Efforts to Improve Shooting Accuracy in Futsal Games Through Structured at UKM Futsal UPI Sumedang - Dhani Daud Firmansyah; Adang Sudrazat; Rizal Ahmad Fauzi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This research is motivated by the low shooting accuracy of futsal players, which is generally caused by suboptimal mastery of basic techniques, poor movement coordination, and the lack of structured and sustainable training programs. In futsal, shooting accuracy is a crucial indicator that directly influences the success of scoring goals. Therefore, a systematic training method is needed to improve this ability. This study aims to determine the effect of structured training on improving shooting accuracy among UPI Sumedang futsal UKM players. The method used was a quantitative approach with a one group pretest-posttest experimental design. The sample consisted of 15 players who actively participated in futsal UKM activities. Data were collected through shooting accuracy tests conducted before (pretest) and after (posttest) the implementation of a structured training program. Data analysis was carried out using statistical tests to determine the differences in results before and after treatment. The results showed a significant improvement in shooting accuracy after the implementation of structured training. This improvement was indicated by the difference in the average scores between pretest and posttest, supported by statistical test results showing a significant effect. These findings indicate that systematic, targeted, and repetitive training effectively improves basic shooting techniques. Furthermore, the improvement was influenced by a combination of technical training, target-based methods, drill exercises, and physical components such as leg muscle explosiveness and eye-leg coordination.